SOCREALIZM AND PRINCIPLE OF IDENTITY IN REFERENT LYRIC - Derkachova, O. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article deals of the feature of the Ukrainian referent poetry. Research is based on to traditional in socrealistic tradition principle of identity. The features of imaginary reference are determined. The principles of image of the world real and iedal in poetic system are analysed.